Transient Waves Due to Mechanical Loads in Elasto-Thermo-Diffusive Solids (Advances in Applied Mathematics and Mechanics, 2011)
This paper deals with the study of transient waves in a homogeneous isotropic,solid half-space with a permeating substance in the context of the theory ofgeneralized elasto-thermodiffusion. The half-space is assumed to be disturbeddue to mechanical loads acting on its boundary. The model comprising of basicgoverning differential equations and boundary conditions has been solved byemploying Laplace transform technique. Noting that the second sound effects areshort lived, the small time approximations of solution for various physicalquantities have been obtained and the results are discussed on the possiblewave fronts. In case of continuous and periodic loads acting at the boundary,the displacement is found to be continuous at each wave front while it is discontinuousin case of impulsive load. The temperature and concentration fields are found to bediscontinuous at all the wave fronts. The displacement, temperature change and concentrationdeviation due to impulsive, continuous and periodic mechanical loads have also been evaluatedin the physical domain at all times by employing numerical inversion technique of integraltransform. The computer simulated numerical results have been presented graphically in respectof displacement, temperature change and concentration deviation for brass. A significant effectof mass diffusion has been observed on the behaviour of mechanical and thermal waves.